Effectiveness of A Surgical Wound Care Bundle for Reducing Surgical Site Infection after Emergency Abdominal Surgery (Sir Salimullah Medical College Journal, 2023)
Background: Surgical site infection (SSI) imposes a considerable financial burden to both hospital and patient by increasing the hospital stay, utilization of resources and readmission rates. This study compared the effectiveness of surgical wound care bundle concept with traditional ongoing wound care for reduction of SSI after emergency abdominal surgery.Methods: This cross-sectional analytical study was carried out in Department of Surgery of SSMC, for one-year period after ethical approval. A total of 120 patients who underwent emergency abdominal surgery were included after taking informed written consent and divided into two groups: Group-A (n=60, surgical wound care bundle) and Group-B (n=60, traditional ongoing care). A detailed history and thorough clinical examination were carried out in each patient. Data were collected in separated case-record form and analyzed by SPSS 24.Results: Mean age of Group A and Group B was 44.88±11.2 years and 44.82±13.3 years accordingly (p=0.391) with male majority in both groups (70% in Group-A and 80% in Group-B, p0.05). Group-B patients had higher frequency of SSI development compared to Group-A (43.3% vs. 15%, p=0.001). Besides, patients having traditional ongoing care had longer hospital duration than surgical wound care bundle (10.1±2.7 vs. 6.9±1.9 days, p